2004
DOI: 10.1111/j.1600-9657.2004.00246.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors related to traumatic dental injuries in Brazilian schoolchildren

Abstract: The aim of this pilot study was to analyse whether overjet, lip coverage and obesity represented risk factors associated with the occurrence of dental trauma in the permanent anterior teeth of schoolchildren in Recife, Brazil. It included a random sample of 116 boys and girls aged 12 years, attending both public and private schools. Data was collected through clinical examinations and interviews. Dental trauma was classified according to Andreasen's criteria (1994). Overjet was considered as risk factor when i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
70
5
30

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(130 citation statements)
references
References 24 publications
17
70
5
30
Order By: Relevance
“…Further, the relationship between the presence of dental trauma and OW (≥85 th percentile BMI) was statistically significant in our study which is in agreement with the findings in the literature [8,9,22]. On the contrary, few other studies did not detect any statistically significant relation between TDI and OW [20,23,24]. Petti et al, [22] had suggested that lower adeptness among the obese individuals make them more prone to these injuries.…”
Section: Discussionsupporting
confidence: 81%
“…Further, the relationship between the presence of dental trauma and OW (≥85 th percentile BMI) was statistically significant in our study which is in agreement with the findings in the literature [8,9,22]. On the contrary, few other studies did not detect any statistically significant relation between TDI and OW [20,23,24]. Petti et al, [22] had suggested that lower adeptness among the obese individuals make them more prone to these injuries.…”
Section: Discussionsupporting
confidence: 81%
“…Ressalta-se que a presença de fraturas nos dentes anteriores, nesse período de vida, tem uma conseqüência bem relevante, pois interfere diretamente na auto-estima das pessoas, trazendo sérias dificuldades nos relacionamentos interpessoais e sociais, visto que a desarmonia no sorriso é considerada uma condição inaceitável para a maioria dos indivíduos. Esse fato se agrava ainda mais, em razão dos incisivos centrais superiores, elementos mais visíveis no sorriso, serem os mais afetados pelo traumatismo dentário, como revelou essa pesquisa e demais estudos 8,6,14,22 . É importante ressaltar que o incisivo central superior esquerdo foi bem mais acometido pelo traumatismo que o direito.…”
Section: Distribuição Em Valores Absolutos Das Fraturas De Acordounclassified
“…Levantamentos realizados no Brasil têm destacado a grande prevalência de traumatismos dentários na dentição decídua e mista, variando de 10,4% a 58%, dependendo da faixa etária e do local em que são coletados os dados [2][3][4][5][6][7][8][9] . Quando o estudo é realizado em ambiente hospitalar, os tipos de traumatismo mais registrados são os deslocamentos (luxações), enquanto que em escolas, domicílio ou consultórios são observados traumatismos de menor magnitude 10 .…”
unclassified
“…There is evidence that the prevalence of TDI is relatively high in many countries. The prevalence of TDIs among adolescents in the Americas and Europe ranged from 15 % to 23% and 23% to 35%, respectively (2,3). Corresponding prevalence rates among adolescents in Asia and Africa ranged from 4% to 35% and 15% to 21% (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…The main reported causes of anterior permanent tooth injuries are falls, collisions with people or inanimate object, traffic accidents, sports and violence (2,8). Predisposing factors include inadequate lip coverage and increased incisal overjet of the teeth (3,6). The majority of dental injuries involve the anterior teeth, which may lead to restriction in biting, difficulty in speaking clearly, and feeling embarrassed to show the teeth.…”
Section: Introductionmentioning
confidence: 99%